THE EFFECT OF KNOWLEDGE MANAGEMENT ON THE STRATEGIC MANAGEMENT PROCESS MEDIATED BY COMPETITIVE INTELLIGENCE IN THE SMALL BUSINESS COMPANY - Didi Sundiman (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2018)
The purpose of this study is to discuss the synergic and separate use of knowledge management and competitive intelligence in stage of strategic management process. This study presents two independent variables (knowledge management and competitive intelligence) and one dependent variable (strategic management process). 145 samples from Indonesia small businesses considered valid, thereby indicating 88.41% validity rate. The results show that the proposed variable, Knowledge management and competitive intelligence significantly influences strategic management process from the perspective of the small business in West Indonesia. This result implies a lack of mediation effect presented by the competitive intelligence. This finding clarifies the research question that knowledge management and competitive intelligence are associated with strategic management process